EFEKTIVITAS METODE PEMBELAJARAN BEYOND CENTERS AND CIRCLE TIME UNTUK PERKEMBANGAN ANAK USIA 5-6 TAHUN - Nurul Hayati; Umu Da’watul Choiro (Nahdlatul Ulama University Sunan Giri Bojonegoro, Indonesia, 2021)
The purpose of this study was to determine the development of aspects of child development through the central learning method. With the formulation of the research problem, How is the implementation of BCCT learning in Early Childhood Development at RA Muslimat NU 05 Jenu, what are the aspects of early childhood development in the implementation of learning with the BCCT approach at RA Muslimat NU 05 Jenu, How is the effectiveness of the implementation of the BBCT learning method in child development Early Age at RA Muslimat NU 05 Jenu?. This study uses a qualitative method, with a descriptive type of approach. With data sources from Principals, Teachers, and Students of group B RA Muslimat NU 05 Jenu, the results of this study are RA Muslimat NU 05 Jenu developed 4 centers namely, Preparation Center, Imtaq Center, Art Center, Cooking Center, with stages, Environmental Footing Play, Foothold Before Play, Foothold During Play, and Foothold After Play which develops 6 aspects of development, namely, the development of religious and moral values, cognitive, physical motor, social emotional, language, art. This research concludes with the average result of Developing According to Expectations in children's development which is considered a good and effective learning method.